"Taking on the Technicalities" of International Law – Practice, Description, Critique: A Response to Fleur Johns. (3rd August 2017) - Sullivan, Gavin
Abstract : By laboring underneath the radar of formal law, using a diverse array of conceptual tools and working from material disregarded by mainstream legal scholarship, Fleur Johns ' research has consistently opened up novel ways of grappling with international legal problems. The article at the focal point of this symposium continues to push the envelope of international legal studies. It sheds light on how the rise of Big Data and algorithmic decisionmaking is transforming international authority. It also speaks to the increasing deformalization of international law. Examining the mundane practices of global governance may sound unrevealing to some. But Johns shows how this approach can yield important insights into international law's operations and effects.